Parts Unknown: Risk Factors of Intimate Partner Violence in Azerbaijan, Kyrgyzstan, Tajikistan, and Moldova - Hayes, Brittany E. (Journal of interpersonal violence, 2021)
Extant research has argued that there are variations in predictors of intimate partner violence (IPV) across nations and it is necessary to examine country-specific correlates of IPV. Much remains unknown about factors that affect risk of IPV in transitional countries. Specifically, we explore risk factors for IPV among four former nations of the Soviet Union—Azerbaijan, Kyrgyzstan, Tajikistan, and Moldova—with data from the nationally representative Demographic and Health Surveys. Rates of physical abuse were similar within Tajikistan (18.96%) and Moldova (18.38%), while Kyrgyzstan (20.62%) had the highest prevalence and Azerbaijan (9.29%) had the lowest prevalence. In contrast, the prevalence of sexual abuse was very similar across the four countries and was much lower (between 1.00% and 3.50%) than cross-national estimates of physical abuse. Findings suggest that many of the same risk factors of IPV in developing and developed nations influence risk of IPV in transitional nations. Across the four former Soviet nations included in analyses, the experience of controlling behaviors, husband’s alcohol use, and witnessing IPV or experiencing abuse during childhood were all significantly associated with risk of physical and sexual abuse later in life. Indeed, the intergenerational transmission of violence may be a cross-national phenomenon. In addition, equality in decision making did not have an effect on risk of physical and sexual violence, except for risk of physical abuse in Moldova. This may be due to the historical context of these nations. Taken together, findings suggest that country context may influence individual risk factors of IPV.